Empowering Palm Oil Smallholders through Biofertilizer Innovation and Policy Integration in Babulu, East Kalimantan: - - Sipahutar, Merry Krisdawati; Indrayani, Indrayani; Kansip, Kansip (Abdimas Universal, 2026)
Palm oil biomass waste in Indonesia, particularly empty fruit bunches (EFB), presents significant environmental challenges while also offering opportunities for sustainable agriculture. This community service program was conducted at the Labangka Village Hall, Babulu Subdistrict, Penajam Paser Utara Regency, East Kalimantan, with the aim of empowering smallholder farmers to convert EFB into microbially enriched biofertilizer and integrate this innovation into local policy frameworks. The program applied a participatory approach through training, hands-on demonstrations, demonstration plots using mung bean (Vigna radiata) as a test crop, and science–policy dialogue involving more than 30 farmers (≥40% women and ≥20% youth). A fertilizer comparison and branding workshop was also conducted to support product commercialization. The results showed increased farmer capacity in biofertilizer production and application, improved soil conditions, enhanced microbial activity, and better plant growth compared to conventional practices. In addition, the initiative facilitated the development of local policy instruments and integration into the Village Government Work Plan (RKP Desa), enabling potential funding through the Village Fund. This program demonstrates a scalable model that integrates technological innovation, community empowerment, and institutional support to promote sustainable agriculture.